Symptoms similar to Kleine–Levin syndrome in a patient with basilar artery occlusion: a case report and literature review - Kong, Linghua; Li, Chunyan (Frontiers in Neurology, 2024)
Introduction Kleine–Levin syndrome (KLS) is a rare disorder characterized by recurrent periodic hypersomnia, cognitive disturbances, hyperphagia, and hypersexuality. Although many factors have been associated with its occurrence, little is known about treatment. Herein, we present a case of symptoms similar to KLS thought to be related to vascular occlusion disease. Case description An 81-year-old woman was admitted to the hospital due to recurring episodes of disturbance of consciousness, cognitive disorder, and hyperphagia for 18 years. She was diagnosed with KLS and basilar artery occlusion. Endovascular and antithrombotic therapy was initiated, and her symptoms fully resolved within 2 weeks of treatment initiation. Conclusion KLS has diverse clinical presentations and demonstrates variable therapeutic responses. Vascular disease or blood flow disorder may be one possible factor for this disease. This case underscores the need for further research into the etiology and pathogenesis of KLS to promote evidence-based approaches for its diagnosis and treatment.